Barriers and Facilitators to Recognition and Reporting of Child Abuse by Prehospital Providers. (2nd January 2017) - Tiyyagura, Gunjan Kamdar; Gawel, Marcie; Alphonso, Aimee; Koziel, Jeannette; Bilodeau, Kyle; Bechtel, Kirsten
Abstract: Background: Prehospital care providers are in a unique position to provide initial unadulterated information about the scene where a child is abusively injured or neglected. However, they receive minimal training with respect to detection of Child Abuse and Neglect (CAN) and make few reports of suspected CAN to child protective services.Aims: To explore barriers and facilitators to the recognition and reporting of CAN by prehospital care providers.Design/Methods: Twenty-eight prehospital care providers participated in a simulated case of infant abusive head trauma prior to participating in one-on-one semi-structured qualitative debriefs. Researchers independently coded transcripts from the debriefing and then collectively refined codes and created themes. Data collection and analysis continued past the point of thematic saturation.Results: Providers described 3 key tasks when caring for a patient thought to be maltreated: (1) Medically managing the patient, which included assessment of the patient's airway, breathing, and circulation and management of the chief complaint, followed by evaluation for CAN; (2) Evaluating the scene and family interactions for signs suggestive of CAN, which included gathering information on the presence of elicit substances and observing how the child behaves in the presence of caregivers; and (3) Creating a safety plan, which included, calling police for support, avoiding confrontation with the caregivers and sharing suspicion of CAN with hospital providers and child protective services. Reported barriers to recognizing CAN included discomfort with pediatric patients; uncertainty related to CAN (accepting parental story about alternative diagnosis and difficulty distinguishing between accidental and intentional injuries); a focus on the chief complaint; and limited opportunity for evaluation. Barriers to reporting included fear of being wrong; fear of caregiver reactions; and working in a fast-paced setting. In contrast, facilitators to reporting included understanding of the mandated reporter role; sharing thought processes with peers; and supervisor support.Conclusions: Prehospital care providers have a unique vantage point in detecting CAN, but limited resources and knowledge related to this topic. Focused education on recognition of signs of physical abuse; increased training on scene safety; real-time decision support; and increased follow-up related to cases of CAN may improve their detection of CAN.